Evolution of complex giant seafloor depressions at the northern Argentine continental margin (SW Atlantic Ocean) under the influence of a dynamic bottom current regime - Warnke, Fynn; Schwenk, Tilmann; Miramontes, Elda; Spiess, Volkhard; Wenau, Stefan; Bozzano, Graziella; Baqués, Michele; Kasten, Sabine (Frontiers in Earth Science, 2023)
Seafloor depressions (SD) are features commonly observed on the ocean floor. They often occur as circular, small-sized (up to 10s of m) incisions caused by fluid expulsion. Larger depressions (100s m to km) are considerably less abundant, and their origin and development have been scarcely studied. This study investigated two giant morphological depressions (>5 km) using recently acquired multibeam bathymetry and backscatter, sediment echosounder, and high-resolution seismic data.. A arc-shaped (SD-N) and a sub-circular depression (SD-S) are located on the Ewing Terrace at the Argentine Continental Margin north and south of the Mar del Plata Canyon, respectively. The study area is influenced by the Brazil-Malvinas Confluence, where major counterflowing ocean currents affect sedimentation, and northward flowing currents form a large contourite depositional system. Using an existing seismo-stratigraphy, the onset of SD-N was dated to the middle Miocene (~15-17 Ma), whereas SD-S started developing at the Miocene/Pliocene boundary (~6 Ma). Acoustic anomalies indicate the presence of gas and diffuse upward fluid migration, and therefore seafloor seepage is proposed as the initial mechanism for SD-S, whereas we consider a structural control for SD-N to be most likely. Initial depressions were reworked and maintained by strong and variable bottom currents, resulting in prograding clinoform reflection patterns (SD-N) or leading to the build-up of extensive cut-and-fill structures (SD-S). Altogether, this study highlights the evolution of two unique and complex seafloor depressions throughout the geologic past under intense and variable bottom current activity in a highly dynamic oceanographic setting.